Assessment of the potential toxicity of glyphosate-based herbicides on the photosynthesis of Nitella microcarpa var. wrightii (Charophyceae). Issue 5 (1st September 2016) - de Campos Oliveira, Régis; Boas, Lucas Kortz Vilas; Branco, Ciro Cesar Zanini
Abstract: Although macroalgae are considered one of the most important primary producers in streams, to our knowledge there has been no research on the effects of herbicides on these organisms. Such studies are crucial for improving our understanding of the impact of these substances on stream ecology. In this study, we assess the effects of technical-grade glyphosate, Roundup and aminomethylphosphonic acid (AMPA; the main degradation product of glyphosate) on the photosynthetic rate, dark respiration rate and chlorophyll a content of Nitella microcarpa var. wrightii, a green algae found worldwide. Three concentrations of technical-grade glyphosate and Roundup were tested (0.28, 3.5 and 6 mg l −1 ), while for AMPA only one concentration was evaluated (0.03 mg l −1 ). Our results indicate that glyphosate has a stronger inhibitory effect on photosynthetic rate when applied in association with a surfactant (Roundup). These effects are related both to the concentration of the active ingredient and to exposure time. On the other hand, treatment with AMPA had a stimulatory effect on the photosynthetic rate, which may be associated with an increased supply of phosphorus available to the algae from the AMPA degradation process. From an ecological perspective, our results show that the ecological distribution of N. microcarpa var. wrightii, in terms of both spatial and temporal scales, can be affected by glyphosate-based herbicides in streams.